IMPROVING THE ABILITY OF YOUNG PLAYERS TO WORK WITH THE BALL IN OUR COUNTRY (Archive of Conferences, 2022)
The article contains information about the attention paid to sports in our country, as well as the theoretical and practical education of young players, as well as techniques and methods.